Estimacion de evapotranspiracion de referencia a nivel mensual en Venezuela. ¿Cual metodo utilizar? - Trezza, R.
(Es, En)
Ilus., 9 ref.
Keywords: EVAPOTRANSPIRACION; ESTIMACION; INFORMES METEOROLOGICOS; VENEZUELA; FAO-56; FAO-24; PENMAN-MONTEITH; HARGREAVES; BIOAGRO